A Novel Hemocyte-Specific Small Protein Participates in White Spot Syndrome Virus Infection via Binding to Viral Envelope Protein - Mingzhe Sun; Shihao Li; Yang Yu; Xiaojun Zhang; Fuhua Li (Viruses, 2023)
Hemocytes are essential components of the immune system against invading pathogens in shrimp. Many uncharacterized transcripts exist in hemocytes but the knowledge of them is very limited. In the present study, we identified a novel small protein from the uncharacterized transcripts in hemocytes of Litopenaeus vannamei. This transcript was specifically expressed in hemocytes and encoded a novel secretory protein, which was designated as hemocyte-specific small protein (LvHSSP). The expression level of LvHSSP was significantly up-regulated in the hemocytes of shrimp infected with white spot syndrome virus (WSSV). After knockdown of LvHSSP by RNA interference, the WSSV copy number in shrimp decreased significantly. Conversely, WSSV copy number increased in shrimp when they were infected by WSSV after incubation with recombinant LvHSSP protein. These results suggested that LvHSSP might promote viral infection in shrimp. Immunocytochemical assay showed that the recombinant LvHSSP protein was located on the membrane of hemocytes. Co-IP results showed that LvHSSP could interact with VP26, the main envelope protein of WSSV, suggesting that LvHSSP might mediate WSSV adhesion and entry into host cells by binding to viral envelope protein. Meanwhile, the total hemocyte counts were significantly decreased after LvHSSP knockdown while increased after supplementing with recombinant LvHSSP protein, supporting the idea of hemocytes as the carrier for systemic dissemination of WSSV. This study reported a novel small protein in hemocytes, which modulated the viral infection in shrimp. Our results will enrich the knowledge of invertebrate innate immunity and provide a new field in the study of hemocyte function.